SYME’S OPERATION IN THE TREATMENT OF GUNSHOT INJURIES OF THE FOOT - Liabakh, Andrii; Turchin, Olena; Yevlantieva, Tetiana; Kharchyk, Vasyl (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
Symeʼs operation for gunshot injuries of the foot may be a viable alternative to transtibial amputation. Objective. To analyze the results of the use of Symeʼs operation in patients with gunshot injuries of the foot, to highlight the important points of surgical technique, rehabilitation and prosthetics. Methods. The results of treatment of 12 men with gunshot wounds to the foot aged 23–54 years (mean age (36.1 ± 2.7) years) who underwent Syme surgery were analyzed. All patients were military personnel at the time of injury. Clinical, instrumental and microbiological examinations were used. The severity of the injury and the prospects of reconstructive treatment were assessed by the Hannover Fracture Score (HFS-97), the anatomic defect present and the severity of static-dynamic disorders. The results were evaluated according to VAS (pain) and ALAC (prosthesis using). Results. Healing of postoperative wounds in all cases occurred without complications. The observation period was from 8 months. up to 7 years (3.5 years on average). All 10 prosthetic patients use a prosthesis: 1 — walking on a prosthesis outside the home (ALAC IV), 5 — independent mobility (ALAC V), 4 — mobility does not differ from the norm (ALAC VI). In two cases (15,4 %) due to pain syndrome (7,3 and 6,8 according to VAS) prosthetics was impossible — reamputation at the level of the leg. Conclusions. Syme’s operation provides a good functional result of prosthetics in case of gunshot injuries of the foot, is a real alternative to transtibial amputation in cases with preserved hindfoot.